Chemically activated biochar derived from mangrove litter with enhanced CO2 adsorption capacity for carbon sequestration - Ariyanti, Dessy; Syifa, Viona; Hapsari, Farida Diyah; Widiasa, I Nyoman; Widayat, Widayat; Silviana, Silviana; Purbasari, Aprilina; Setiabudi, Herma Dina; Hamzah, Fazlena (International Journal of Renewable Energy Development, 2026)
Overcoming climate change is crucial to ensure environmental sustainability. This research focuses on the development of chemically activated biochar (CAB) from mangrove litters that can be used for CO2 adsorption, which leads to reducing the impacts of climate change. The synthesisation of CAB was carried out via pyrolysis at 400℃ for 2 hours under nitrogen gas flow, followed by treatment using various activating agents (0.1 M of H2SO4, HCl, KOH, and NaOH) for 2 hours with a biochar-to-solution ratio of 1 g : 4 mL. The activation process was designed to enhance surface area, pore characteristics, and functional groups associated with CO2 adsorption performance. The observation on the characteristics of CAB using Scanning Electron Microscope and Energy Dispersive X-Ray (SEM-EDX), The Brunauer, Emmett, Teller and Barret-Joyner-Halenda (BET-BJH), Fourier Transform Infrared Spectroscopy (FTIR), CHN Analyser, and static batch CO2 adsorption tests shows the ability of CAB in capturing CO2 through several possible mechanism. Among the samples, KOH-activated biochar (B-KOH) exhibited the highest CO2 adsorption capacity, reaching 12.47 mmol CO2 g-1 biochar. This high performance is attributed to a potassium (K) composition of 9.74%, which effectively catalyzed the development of a microporous structure, resulting in a micropore volume of 5.927 x 10-3 cm3/g and an optimized average pore width of 1.543 nm. Furthermore, B-KOH maintained the highest O-H group area (1.533 a.u. x cm-1), enhancing its affinity for CO2 molecules. This research offers an innovative and practical solution to reduce greenhouse gases and is expected to have a significant impact, both locally and globally, in advancing sustainable development.